OPG gene-modified adipose-derived stem cells improve bone formation around implants in osteoporotic rat maxillae - Yingbiao Wan; Chen Hu; Yongjie Hou; Chenchen Si; Qian Zhao; Zhenzhen Wang; Liyuan Wang; Xiaoqian Guo (Heliyon, 2023)
Background: Osteoporosis is a significant barrier to the use of dental implants in the elderly for the treatment of tooth defects. Adipose derived stem cells (ADSCs) have demonstrated extensive potential for tissue repair and regeneration. The present study aimed to investigate the effectiveness of ADSCs engineered to express high levels of osteoprotegerin (OPG) for the treatment of bone loss in implant dentistry caused by estrogen deficiency. Methods: A rat model of osteoporosis was established through double oophorectomy, and the rats were treated by gene modified cells Adv-OPG-ADSCs. The effects of the treatment on maxilla tissue changes were evaluated using HE staining and micro-CT. Additionally, ALP and TRAP staining were used to assess osteoblast and osteoclast alterations. Finally, the changes in related osteoblast and osteoclast indicators were measured by RT-qPCR, Western blot, and ELISA. Results: The successfully generated high-OPG-expressing ADSCs led to increase of cell viability, proliferation, and osteoblast differentiation. Treatment with Adv-OPG-ADSCs significantly ameliorated maxillary morphology, trabecular volume reduction, and bone mineral density decline in the model of estrogen-deficient maxillary implant dentistry. Furthermore, the treatment was beneficial to promoting the generation of osteoblasts and inhibiting the generation of osteoclast. Adv-OPG-ADSCs increased OPG, ALP, OCN, and Runx-2 expressions in the maxilla while suppressing RANKL expression, and also increased the concentration of COL I and PINP, as well as decreased the concentration of CTX-1. Conclusion: Adv-OPG-ADSCs promote the formation of osteoblasts and inhibit the generation of osteoclasts, thereby inhibiting bone absorption, facilitating bone formation, and promoting the repair of maxillary bone after dental implantation in the presence of osteoporosis-related complications, especially in the setting of estrogen deficiency, providing scientific basis for the application of Adv-OPG-ADSCs in the treatment of implant related osteoporosis.